ANALISIS PELUANG PENGGUNAAN LAYANAN KEUANGAN DIGITAL (LKD) PADA MASYARAKAT KABUPATEN ACEH BESAR PROVINSI ACEH - Chenny Seftarita; Uliya Azra (Universitas Teuku Umar, 2018)
This research to determine the willingness of the public who want use digital financial services. this research was conducted in Aceh Besar Regency by taking200 samples randomly in several villages. The model used in this research is a logit model. The results of research showed that of the variable income, distance to the center of the economy, distance to the nearest bank, and a signal service, there is only one variable is significant and positive impact on the desire to use financial services digital, variable distance to the nearest bank while a variable distance to the center of the economy negative and not significant. Based on the research that has been done, a lot of people who are less aware Financial Services Digital and some people still make less use of banking services. Researchers recommended that the government and Bank Indonesia participated socialize the Financial Services Digital.Keyword : Aceh Besar, Digital financial services, Logit modeteks